1998
DOI: 10.1073/pnas.95.8.4635
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence that erythropoietin protects neurons from ischemic damage

Abstract: Erythropoietin (EPO) produced by the kidney and the liver (in fetuses) stimulates erythropoiesis. In the central nervous system, neurons express EPO receptor (EPOR) and astrocytes produce EPO. EPO has been shown to protect primary cultured neurons from N-methyl-D-aspartate (NMDA) receptor-mediated glutamate toxicity. Here we report in vivo evidence that EPO protects neurons against ischemia-induced cell death. Infusion of EPO into the lateral ventricles of gerbils prevented ischemia-induced learning disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
657
1
17

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 884 publications
(698 citation statements)
references
References 46 publications
23
657
1
17
Order By: Relevance
“…10 U/mL) did not show stronger protective effects. Several studies have confirmed this particular dose-response behavior of EPO in vivo [17,18] , which might have relevance to the design of the upcoming clinical trials. As the recent human stroke study has demonstrated, EPO has beneficial effect on neurons in the context of cerebral ischemia [19] .…”
Section: Discussionsupporting
confidence: 57%
“…10 U/mL) did not show stronger protective effects. Several studies have confirmed this particular dose-response behavior of EPO in vivo [17,18] , which might have relevance to the design of the upcoming clinical trials. As the recent human stroke study has demonstrated, EPO has beneficial effect on neurons in the context of cerebral ischemia [19] .…”
Section: Discussionsupporting
confidence: 57%
“…Erythropoietin reduces neuronal death with OGD, 86 glutamate toxicity, 91 and NO-induced cell death. 92 Astrocytes contribute to the EPO-mediated neuroprotection, as demonstrated by experiments in which conditioned media taken from hypoxic astrocyte cultures is protective to neurons exposed to OGD. 39 To reduce ischemic damage in the brain, neuroprotectants would need to reduce cell death of both neurons and astrocytes.…”
Section: Astrocytes and Epo As A Neuroprotectantmentioning
confidence: 99%
“…Interestingly, recombinant human EPO (rhEPO) treatment has recently been reported to have such effects (ie to increase the expression of BDNF in the brain; Zhang et al, 2006). Furthermore, several studies have shown that rhEPO is a potent neuroprotective agent against neural dysfunction resulting from a variety of neural insults that involve increased apoptosis (Sakanaka et al, 1998;Siren et al, 2001a;Dzietko et al, 2004;Spandou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%